‘The doctors were more knowledgeable about what I had’: patient views on the value of point-of-care tests for managing respiratory infections. A qualitative study in European primary care - Wanat, Marta; Hoste, Melanie Eugenie; Anastasaki, Marilena; Böhmer, Femke; Colliers, Annelies; Gkamaletsou, Maria; Löffler, Christin; Lionis, Christos; Malania, Lile; Shah, Mala; Wollny, Anja; Vellinga, Akke; et al. (BJGP open, 2025)
Point-of-care tests (POCT) can support diagnosis of patients with community-acquired acute respiratory tract infections (CA-RTI) in primary care and thereby reduce uncertainty whether antibiotics may benefit patients. However, successful roll out of POCTs need to be built on a deep understanding of patients' perspectives on the place of POCTs in patient-centred care. To explore patients' perceptions of the value of POCTs during consultations for CA-RTI. A qualitative study using semi-structured interviews in Belgium, Republic of Ireland, Georgia, Germany, Greece, and the UK with patients who consulted for CA-RTI in primary care. Interviews were audio recorded, transcribed, and analysed using reflexive thematic analysis. Interviews with 56 participants revealed that in the process of a GP making a diagnosis and treatment decision, patients valued several components, such as a physical examination, their GP enquiring about and listening to concerns, and a POCT. Yet, the visibility and relative importance of each of these components varied in the four main ways in which patients perceived the value of POCTs, including 1) test as objective evidence compared to 'subjective' clinical judgment; 2) test as providing more precision; 3) test as inferior to clinical judgment; 4) test as one of the tools in the GP's toolbox. The wide variation in patient perceptions about POCT for CA-RTI underscores the importance of recognising patient preferences regarding the diagnostic process. This understanding is important to ensure that POCT results optimally influence treatment decision-making, patient satisfaction, and acceptance of their care plan.